A Study on Illegal Wildlife Trade Based on Analytic Hierarchy Process and ARIMA Model - Ma, Yiyang (International Journal of Computer Science and Information Technology, 2024)
This study delves into the pressing global issue of reducing illegal wildlife trade, with a specific emphasis on elephants, given their paramount ecological, economic, and ethical importance [1]. Through a methodical approach, we meticulously evaluate potential clients using the Analytic Hierarchy Process, aiming to discern their suitability based on factors such as power, resources, and interest. Additionally, we develop the Illegal Trade in Elephants Prediction Model, utilizing advanced ARIMA forecasting techniques and time series analysis to project future trade scales. Complementing this, a comprehensive resource allocation strategy is devised through a sophisticated linear regression and programming model, considering a myriad of factors including political and financial support, technical expertise, and conservation strategies. We meticulously analyze key indicators over time to gauge the efficacy of our intervention efforts, utilizing both ARIMA and linear regression models to demonstrate a decline in illicit activity and an enhancement in program success rates.